Analysis of Ecotourism-Based Science Learning Materials: A Case Study of Tourism in Pemepek Village - Irman Muliadi; Ade Irama; M. Zannatun Naeem Zana (Journal of Biology, Environment, and Edu-Tourism, 2026)
Despite the growing recognition of ecotourism as an educational resource, the systematic integration of local sites into formal science curricula remains underexplored in rural Indonesian contexts. This study analyzes the potential of three ecotourism destinations in Pemepek Village, Central Lombok: Lembah Datu, Pindah Alam, and Forest Area with Special Purpose (FAWSP) Rarung, or KHDTK Rarung, as contextual science learning materials for elementary and junior high school levels. Employing a qualitative descriptive approach, the research used field observations and science concept rubrics to identify educational themes and analyzed the data using the Miles and Huberman interactive model. The findings reveal that each site offers distinct scientific content: Lembah Datu provides insights into riparian ecosystems and simple machines; Pindah Alam facilitates learning on the hydrological cycle, hydrostatic pressure, and renewable energy; and KHDTK Rarung supports the study of biodiversity, symbiosis, and biotechnology. Collectively, these destinations function as "nature laboratories" that bridge abstract scientific theory with real-world observation. By synthesizing these findings, the research contributes an ethnoscience-based framework that guides educators in developing innovative, place-based curriculum strategies. Ultimately, this study demonstrates how local ecotourism can be transformed into a pedagogical tool to enhance scientific literacy through direct environmental engagement.